The prevalence of emotional abuse in children living in Sub-Saharan Africa - a systematic review - Kurtz, Marie; Kawka, Hannah; Horstick, Olaf; Brenner, Stephan; Deckert, Andreas; Louis, Valérie R.; Winkler, Volker; Wilson, Michael; Bärnighausen, Till; Dambach, Peter (Child abuse & neglect, 2023)
Objectives - This study is meant to put a focus on the prevalence of emotional abuse in low-income states like the Sub-Saharan region. - Methodology - Searching PubMed, Google scholar, and web of science during February and April 2021 a total of 2264 articles were identified, 27 met the inclusion criteria. We added the results of 13 VAC (Violence Against Children and Youth) studies, conducted by UNICEF capturing information about experienced sexual, physical, or emotional violence in 13-24-year-olds, as well as 56 MIC (Multiple Indicator Cluster) studies, conducted by the CDC to research the disciplinary methods used with children aged 1-14 years in the past month by older household members. Finally, in a meta-analytic approach, we aimed to calculate a pooled estimate of the prevalence. - Results - The included studies depicted a wide range in prevalence rates across countries. For example, while the VAC study in Lesotho in 2018 showed low incidence rates of emotional violence (6.9 % Females, 3.8 % Males), the average prevalence recorded by the MIC study was as high as 57.8 % for females and 59.2 % for males. On average, the MIC studies displayed a higher incidence and the discrepancy of prevalence of emotional abuse between females and males was small. Calculating a pooled estimate of the prevalence was not possible, due to the heterogeneity of the data. - Conclusions - In general countries displayed a high prevalence. A standardized use of a uniform definition of emotional abuse might help to display a more homogenous data set in the future, giving the opportunity for pooled estimates of prevalence.